Fenomena Campur dan Alih Kode dalam Lirik Lagu YUI: Sebuah Kajian Sosiolinguistik - Ayu Azhariyah; Nursidah; Imelda (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang, 2025)
Code-mixing refers to the use of elements from one language inserted into an utterance that basically uses another language. In general, code-mixing can be classified into three types, namely insertion, alternation, and lexical congruence. Meanwhile, code-switching is a term used to describe the switch in the use of one or more languages or language varieties in one communication context, which consists of three main forms: tag, intersentential, and intrasentential. This study aims to identify the intensity of occurrence of words, phrases, and sentences in YUI song lyrics that show symptoms of code-switching and code-mixing, as well as to describe their types. Using the descriptive method, data were collected from 30 song titles, then classified and analyzed systematically. The results showed that the phenomenon of code-switching was found in the form of words as much as 28 data, phrases as much as 47 data, and sentences as much as 85 data. Meanwhile, code-mixing is identified in the form of words as much as 21 data, phrases as much as 44 data, and sentences as much as 15 data